Cartografias de um campo invisível: os anônimos jogadores do futebol brasileiro - Dantas, Marina de Mattos (2017)
The professional soccer and its effects in the production of subjectivities in the profession of player. This is the theme that guides this research which, on the basis of previous research about the dream of being a player and the performance of sport psychology in basic categories, aims to compose a cartography of the reality of the player who professionalizes, but does not occupy the positions of greater emphasis on large "shopping" of soccer nationally and internationally. Are these players generally considered by clubs, entrepreneurs and also by the public as products of less value in the market, but needed to maintain the operation of the competitions of the machine of professional soccer that attracts fans and investors while circulating anonymously by Australian soccer to as coadjuvants of soccer venues. In this sense, it is mapping practices of contemporary soccer, along with the studies of Michel Foucault on the government of the living, along with the studies of researchers in the area of humanities and social sciences about professional soccer. It seeks so to understand the governmentality of soccer venues; the effects of discipline and controls regulators in the production of modes of life of soccer players anonymous professionals; for where these circulating after the departure of the basic categories; catches, potential and resistance that keeps them in the profession and the effect socio-political produced from this reality